Demographics and targeted biopsy with NBI in head and neck mucosal lesions - Bhandari, Pranay; Sachdeva, Kavita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: It is estimated that by the end of year 2020 over 10 million people worldwide would die of cancer every year and about 66% of these would be from developing world like India (WHO-UCC 2003). Our aim in present study was to evaluate the use of targeted biopsy of mucosal lesions of head and neck cancer using narrow band imaging technique, in order to yield more accurate specimen of lesion which will result in correct diagnosis of disease early and to study different demographics of patients. Methods: Patients lesions were examined under NBI endoscope, best site of biopsy were identified on the basis of increase vascularity, neo-angiogenesis and superficial capillary vessels. Biopsy were taken from this site and sent for histopathological examinations. Considering histopathological report as standard, results from NBI endoscopy were compared to the results of previous studies and conclusion was done. We also studied different demographics of these patients under site of lesion, age distribution, sex distribution, and locality, histopathology type. Results: Maximum lesions were found in oral cavity (56.33%). Malignancy was also more common in oral cavity (63.46%), mostly belong to squamous cell carcinoma on histopathology. Mean age of presentation of head and neck mucosal lesion was found to be 48 year and of malignant lesions is 54 years. Conclusions: We conclude that up to an extent with progression of age malignant lesions increase. Male to female ratio of mucosal lesions is 1.7:1 and of malignancy is 2.25:1. Narrow band imaging endoscopy helps us to identify best site of biopsy, helping in early diagnosis of disease and ultimately reducing morbidity and mortality of patient.